HUBUNGAN TUGAS KESEHATAN KELUARGA DENGAN ACTIVITY DAILY LIVING PADA LANSIA YANG MENGALAMI KETERBATASAN FISIK DI WILAYAH KERJA PUSKESMAS LIMO - Safa marwah ilmanan rachmah putri setiawan (2023)
Physical limitations in the elderly occur due to various declines in organ function in the elderly's body as they get older. This problem makes the elderly unable to carry out daily activities independently and another consequence is that it has an impact on the level of dependence of the elderly, both those who later depend on tools and with their families. The study aims to determine the relationship between family health tasks and daily living activity in the elderly who experience physical limitations in the working area of the Limo Health Center in 2023. This research is a quantitative study using a cross-sectional approach, the population in this study are elderly people with physical limitations using the simple random technique. sampling of 85 elderly and their families who cared for them using the Family Health Assignment Questionnaire sheet as an instrument and observation using the Barthel index. Families are considered capable of carrying out Family Health Tasks well with a percentage (54.1%), and more results (45.9%) of the elderly experience total dependency. There is a relationship between Family Health Tasks and Activity Daily Living in the Elderly with Physical Limitations, it can be seen based on p value = 0.001 < α 0.05. This research is expected to increase the implementation of Family Health Tasks on the independence of the elderly through counseling efforts.